Estúrdias estórias - o contador de estórias em "Campo Geral", de Guimarães Rosa - Rodrigues, José Lourenço Becco (2005)
Guimarães Rosa was a storyteller. Throughout all his literary work, there are many storys, in all sizes and kinds. The characters who tell these stories are as important as the stories themselves. Among the many storytellers found in the pages of Corpo de baile we can remark the boy Miguilim, in “Campo Geral”. Within these pages, we tried to understand the act of storytelling as a major factor in the growing process of Miguilim. He and the other children who are storytellers have a creative gift that make them distinct to the tradicional storytellers, the adults. In order to assay that , we compared the children storytellers (in Primeiras estórias) to Joana Xaviel and the old Camilo, traditional grown-up storytellers in “Uma estória de amor”. After that, we focused on the stories that Miguilm makes up/tells, pointing out the moment they are told, what motivates her making of, and their function in the narrative. We take these stories as part of a communicative process (though entirely fictional), that’s why it’s very important to know their context and audience. After all, we compare the narrative of “Campo geral” to the only text of the oral literature quoted by Miguilim: “Hansel and Gretel”. Many of the symbols and metaphors of the fairy tale were taken to the Guimarães Rosa’s literary piece, as an essential part of its themes and conflicts.